Conferring DNA virus resistance with high specificity in plants using virus-inducible genome-editing system - Ji, Xiang; Si, Xiaomin; Zhang, Yi; Zhang, Huawei; Zhang, Feng; Gao, Caixia (Genome Biology, 2018)
The CRISPR/Cas9 system has recently been engineered to confer resistance to geminiviruses in plants. However, we show here that the usefulness of this antiviral strategy is undermined by off-target effects identified by deep sequencing in Arabidopsis. We construct two virus-inducible CRISPR/Cas9 vectors that efficiently inhibit beet severe curly top virus (BSCTV) accumulation in both transient assays (Nicotiana benthamiana) and transgenic lines (Arabidopsis). Deep sequencing detects no off-target effect in candidate sites of the transgenic Arabidopsis. This kind of virus-inducible genome-editing system should be widely applicable for generating virus-resistant plants without off-target costs.